1994
DOI: 10.1128/aac.38.11.2553
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of a new antifungal triazole, D0870, against Candida albicans isolates from oral cavities of patients infected with human immunodeficiency virus

Abstract: We investigated the in vitro activity of a new antifuingal triazole, D0870, against 100 Candida albicans isolates from the oral cavities of patients infected with human immunodeficiency virus by using a broth macrodilution method following the recommendations provided by the National Committee for Clinical Laboratory Standards (document M27-P). All (4,8,10,21). No data are available about its in vitro activity against Candida albicans isolates from the oral cavities of human immunodeficiency virus (HIV)-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We found that for isolates for which fluconazole MICs were high, voriconazole MICs were proportionally higher than those for non-fluconazole-resistant C. albicans isolates (MIC Ͻ 25 g/ml), which may indicate crossresistance. Barchiesi et al reported similar results for the triazoles itraconazole and D0870 against fluconazole-susceptible and -resistant C. albicans isolates in HIV-infected patients (1,2).…”
Section: Discussionmentioning
confidence: 72%
“…We found that for isolates for which fluconazole MICs were high, voriconazole MICs were proportionally higher than those for non-fluconazole-resistant C. albicans isolates (MIC Ͻ 25 g/ml), which may indicate crossresistance. Barchiesi et al reported similar results for the triazoles itraconazole and D0870 against fluconazole-susceptible and -resistant C. albicans isolates in HIV-infected patients (1,2).…”
Section: Discussionmentioning
confidence: 72%
“…Recently, several studies have called attention to the occurrence of primary or acquired infections due to yeast resistant to antifungal drugs. Such reports are more frequent among patients with AIDS or malignant hematological diseases, situations in which the prophylactic or therapeutic use of antimycotics is more disseminated (28)(29)(30) The literature includes many studies which evaluate the susceptibility profile of yeast isolates from different biological fluids and tissues; however, none were found describing the antifungal susceptibility profile of yeast isolates from ocular infections (31)(32)(33)(34)(35) . Considering the high therapeutic failure rate associated with ocular fungal infections, the investigation of the antifun- gal susceptibility profile of ocular fungal pathogens may be useful to identify antifungal resistance as a possible risk factor for unfavorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These secreted proteinases were detected in the range of 30^95 kDa. Inspection of the gelatin gels revealed the presence of at least three (53, 58 and 95 kDa), ¢ve (64, 72, 76, 85 and 95 kDa), six (48, 53, 58, 64, 85 and 95 kDa) and seven (30,34,42,48, 53, 72 and 95 kDa) distinct proteolysis halos in acidic pH (5.5), in the A, B, C and D pattern, respectively (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mucosal candidiasis in AIDS patients is often difficult to treat and recurrences of the infections are frequent even after appropriate antifungal treatments, suggesting an increased potential of C. albicans to attack the debilitated host. Thus, it is likely that C. albicans participates actively in determining the nature of mucosal infection with its own virulence factors [42].…”
Section: Discussionmentioning
confidence: 99%